2020
DOI: 10.1038/s41598-020-62035-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeted DNA demethylation of the Fgf21 promoter by CRISPR/dCas9-mediated epigenome editing

Abstract: Recently, we reported ppARα-dependent DNA demethylation of the Fgf21 promoter in the postnatal mouse liver, where reduced DnA methylation is associated with enhanced gene expression after ppARα activation. However, there is no direct evidence for the effect of site-specific DNA methylation on gene expression. We employed the dCas9-SunTag and single-chain variable fragment (scFv)-TET1 catalytic domain (TET1CD) system to induce targeted DnA methylation of the Fgf21 promoter both in vitro and in vivo. We succeede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 44 publications
0
26
0
1
Order By: Relevance
“…Several studies have proven that FGF21 stimulates the brown (BAT) and beige adipose tissue thermogenesis, which lowers body weight and improves insulin sensitivity in mice ( 73 , 74 ). It has also been reported that the Fgf21 promoter could be demethylated by CRISPR/dCas9-mediated epigenome editing ( 75 ). Therefore, we tried to activate FGF21 in mouse liver to regulate energy homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have proven that FGF21 stimulates the brown (BAT) and beige adipose tissue thermogenesis, which lowers body weight and improves insulin sensitivity in mice ( 73 , 74 ). It has also been reported that the Fgf21 promoter could be demethylated by CRISPR/dCas9-mediated epigenome editing ( 75 ). Therefore, we tried to activate FGF21 in mouse liver to regulate energy homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“… Lau and Suh (2018) successfully demonstrated this by targeting a CGG expansion mutation in the 5'-untranslated region (5'-UTR) of the fragile X mental retardation 1 ( FMR1 ) gene in Fragile X syndrome (FXS) patients, which is the most common form of genetic intellectual disability in males. Several studies have shown CRISPR/dCas9-TET1 capable of removing up to 90% of targeted methylations, significantly increasing gene expression at the target sites ( Liu et al, 2016 ; Morita et al, 2016 ; Hanzawa et al, 2020 ; Horii et al, 2020 ). Horii et al (2020) also used this technology successfully to generate an epigenetic disease model in mice via targeted demethylation of the epigenome.…”
Section: Crispr/cas Precision Genome Editingmentioning
confidence: 99%
“…Hanzawa et al used the dCas9-SunTag-scFv-sfGFP-TET1CD fusion vector for demethylation of the Fgf21 promoter (Table 2) (Hanzawa et al 2020). In this system, dCas9 was fused to SunTag epitopes for recruiting multiple copies of antibody-fused TET1 for enhanced demethylation activities at the target site (Fig.…”
Section: Targeted Promoter Demethylationmentioning
confidence: 99%
“…The dCas9-SunTag-TET1 vector with a single-chain variable fragment (scFv) was used to target the Fgf21 promoter for demethylation in the adult mouse liver (Fig. 2b) (Hanzawa et al 2020). This study also showed that regulation of gene expression is achieved by a site-specific epigenetic tool without altering the DNA sequence in vivo.…”
Section: In Vivo Dna Methylation and Demethylation Studiesmentioning
confidence: 99%